2002
DOI: 10.1006/eujc.2002.0589
|View full text |Cite
|
Sign up to set email alerts
|

Constructing an Infinite Family of Cubic 1-Regular Graphs

Abstract: A graph is 1-regular if its automorphism group acts regularly on the set of its arcs. Miller [J. Comb. Theory, B, 10 (1971), 163-182] constructed an infinite family of cubic 1-regular graphs of order 2 p, where p ≥ 13 is a prime congruent to 1 modulo 3. Marušič and Xu [J. Graph Theory, 25 (1997), 133-138] found a relation between cubic 1-regular graphs and tetravalent half-transitive graphs with girth 3 and Alspach et al. [J. Aust. Math. Soc. A, 56 (1994), 391-402] constructed infinitely many tetravalent ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…It may be shown that all cubic 1-regular Cayley graphs on the dihedral groups are exactly those graphs generalized by Miller's construction. Recently, more 1-regular cubic graphs were constructed by the authors [15][16][17]. Also, as shown in [40] or [41], one can see an importance of a study for cubic 1-regular graphs in connection with chiral (that is regular and irreflexible) maps on a surface by means of tetravalent half-transitive graphs or in connection with symmetries of hexagonal molecular graphs on the torus.…”
Section: Introductionmentioning
confidence: 99%
“…It may be shown that all cubic 1-regular Cayley graphs on the dihedral groups are exactly those graphs generalized by Miller's construction. Recently, more 1-regular cubic graphs were constructed by the authors [15][16][17]. Also, as shown in [40] or [41], one can see an importance of a study for cubic 1-regular graphs in connection with chiral (that is regular and irreflexible) maps on a surface by means of tetravalent half-transitive graphs or in connection with symmetries of hexagonal molecular graphs on the torus.…”
Section: Introductionmentioning
confidence: 99%
“…The first one is alter-incomplete with alter-sequence (2, 4), whereas the second one is alter-complete with alter-sequence (3,12). As in the previous two examples F(L(Q 3 ); H 1 ) is disconnected and not semisymmetric.…”
Section: Line Graphs Of Cubic Graphs and The Associated Generalized Fmentioning
confidence: 81%
“…The line graph of the graph F56A in row 28 in Table 1 is an example of such a graph with alter-exponent 2. In fact, F56A is the smallest member of an infinite family of 1-regular Z k 2 +k+1 -covers of Q 3 (given in [12]), for which the corresponding line graphs are 1 2 -arc-transitive of alter-exponent 2. It may be easily seen that these graphs are alter-incomplete with alter-sequence [2(k 2 + k + 1), 4(k 2 + k + 1)].…”
Section: Alter-exponent Of Tetravalent 1 2 -Arc-transitive Graphsmentioning
confidence: 99%
“…However, all known examples of 1-arc-regular trivalent graphs are Cayley graphs and have soluble automorphism groups. Moreover it was shown in [7] In this paper, we first discuss question (a) and prove that if G is soluble then must be a Cayley graph of a subgroup of G. Then we turn to questions (b) and (c) by considering 1-arc-regular trivalent Cayley graphs of a finite nonabelian simple group. We give a sufficient condition under which one can guarantee that Cay(G, S) is 1-arc-regular.…”
Section: The Graph Is Called (G S)-arc-transitive If G Acts Transitimentioning
confidence: 97%
“…In the literature, the first example of 1-arc-regular trivalent graphs was given by Frucht [4] in 1952. Much later, some other examples were given in [3,13], and very recently more examples were obtained in [7][8][9]. However, all known examples of 1-arc-regular trivalent graphs are Cayley graphs and have soluble automorphism groups.…”
Section: The Graph Is Called (G S)-arc-transitive If G Acts Transitimentioning
confidence: 98%